2014
DOI: 10.1371/journal.pone.0112558
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Use of Proton Pump Inhibitors and the Risk of Hypomagnesemia: A Systematic Review and Meta-Analysis

Abstract: BackgroundAlthough many case reports have described patients with proton pump inhibitor (PPI)-induced hypomagnesemia, the impact of PPI use on hypomagnesemia has not been fully clarified through comparative studies. We aimed to evaluate the association between the use of PPI and the risk of developing hypomagnesemia by conducting a systematic review with meta-analysis.MethodsWe conducted a systematic search of MEDLINE, EMBASE, and the Cochrane Library using the primary keywords “proton pump,” “dexlansoprazole,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 44 publications
2
88
3
5
Order By: Relevance
“…Unlike other studies [9,10] we found that PPI risk factors for hypomagnesemia were higher among patients taking PPI for less than one year, although severe hypomagnesemia was recorded among patients taking them for longer. Future prospective studies analyzing serum magnesium before PPI therapy are needed to clarify the causal relationship better between PPI and hypomagnesemia.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other studies [9,10] we found that PPI risk factors for hypomagnesemia were higher among patients taking PPI for less than one year, although severe hypomagnesemia was recorded among patients taking them for longer. Future prospective studies analyzing serum magnesium before PPI therapy are needed to clarify the causal relationship better between PPI and hypomagnesemia.…”
contrasting
confidence: 99%
“…The prevalence of hypomagnesemia among the patients taking PPI in our study was similar to that reported in a recent review and metaanalysis [9]. Unlike other studies [9,10] we found that PPI risk factors for hypomagnesemia were higher among patients taking PPI for less than one year, although severe hypomagnesemia was recorded among patients taking them for longer.…”
supporting
confidence: 89%
“…systolic versus diastolic HF and HF with preserved versus reduced ejection fractions), because of the absence of such data. Though we adjusted for several confounders, there was a possibility of residual confounding due to other unmeasured confounders (such as proton pump inhibitors and other medications that affect serum magnesium levels (47) and are associated with risk of CVD (48)), which could in part explain the association between serum magnesium and HF. The study included only male Caucasians and cannot necessarily be extrapolated to women and other ethnicities.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The association between PPI use and magnesium levels varies by whether patients concurrently use diuretics. In patients taking diuretics, concurrent use of PPIs was associated with lower adjusted serum magnesium compared to patient not taking diuretics (1)(2)(3)(4). By contrast the occurrence of hypercalcaemia in the context of hypomagnesaemia is unusual.…”
Section: Introductionmentioning
confidence: 99%